Isolation and Characterization of Nutrient-Providing Microbes from Waste Soil and Grass Soil for Bio-Organic Fertilizer Formulation - Mas Alvy Dwi Sayaza; Ilma Nadia Wardani; Abner Atmajendra Waluyaning Jati; Alya Wydia Utami; Ram Muhammad Zidan; Izzah Zen Salsabila Putri; Muhammad Amin Nur Zamzamy; Rima Sri Wahyuni (Jurnal Rekayasa Lingkungan dan Biosistem, 2025)
Intensive agricultural practices have degraded soil fertility, increasing dependence on chemical fertilizers. This study aimed to isolate and characterize nutrient-providing microbes from waste soil and grass soil at IPB University and formulate them into bio-organic fertilizer. Rhizobium was isolated from peanut root nodules using YEMA medium, potassium solubilizing microbes (KSM) from grass soil using Alexandrov medium, and phosphate solubilizing microbes (PSM) from waste soil using Pikovskaya medium. Results showed Rhizobium population of 700 CFU with typical morphology. KSM population reached 1,036,333 CFU/g soil, while PSM reached 1,255,833 CFU/g soil. Both KSM and PSM demonstrated positive solubilization activity with indices of 2.34–2.66. Antagonism tests confirmed compatibility among the three isolates. Bio-organic fertilizer was successfully formulated by combining compost, molasses (5%), and the three microbial isolates in pellet form. Indigenous microbes from different soil ecosystems show promising potential as biofertilizer agents providing balanced N, P, and K nutrients through sustainable biological mechanisms.